استخدام الأنترنت في إنجاز مذكرات شهادة الماستر - لعبيدي, هاجر; بيوضة, إيثار (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة إلى استكشاف استخدامات طلبة السنة الثانية ماستر للم اإعلام اااتصاا جاامةة الماي للأنترنت في إنجاز مذكرات تخرجهم.امن أجل ذلك، التمدنا المنهج المصفي اأسلمب المسح. اأجريت الدراسة للى لينة غير احتمالية تم اختيارها بطريقة قادية. كما التمدنا للى أياة ااتستبيان كأياة أساسية لجمع البيانات.اخلات الدراسة إلى: - ات يمكن تجاهل استخدامات ااتنترنت خاصة في مجا البحث الةلمي اإلداي البحمث الةلمية لأنها صةتبر من أهم اسائل التكنملمجيا الحديثة اهي خزان من المةلممات. - مشاركة الطلبة الجامةيين في المرشات التي صةني بمستجدات التقنيات الحديثة اآخرها الذكاء ااتصطنالي اصدريب للى كيفية التةريف باستخدامات ااتنترنت اكيفية استخراج المةلممات الاحيحة االدقيقة اتختاار المقت االجهد للى أللى قدر ممكن. Study summary: The study aimed to explore the uses of the second year students, Master of Media and Communication at the Wadi University of the Internet, in completing their graduation notes. To this end, we adopted the descriptive approach and the survey style. The study was conducted on an unbearable sample that was selected in a intentional way. We also relied on the questionnaire tool as a basic data collection tool. The study concluded: - The uses of the Internet, especially in the field of scientific research and the preparation of scientific research, cannot be ignored because it is considered one of the most important means of modern technology, which is a tank of information. - The participation of university students in the workshops that mean the developments of modern technologies, the most recent of which is artificial intelligence and training on how to define the Internet uses and how to extract the correct and accurate information to shorten the time and effort as much as possible..
مذكرة ماستر أعلام وإتصال
Keywords: use - the Internet - scientific research - the Internet in scientific research.; ااتستخدا ااتنترنت البحث العلمي الأنترنت في البحث العلمي